2014
DOI: 10.4012/dmj.2013-221
|View full text |Cite
|
Sign up to set email alerts
|

Titanium surface hydrophilicity enhances platelet activation

Abstract: Titanium implant surface modification is a key strategy used to enhance osseointegration. Platelets are the first cells that interact with the implant surface whereupon they release a wide array of proteins that influence the subsequent healing process. This study therefore investigated the effect of titanium surface modification on the attachment and activation of human platelets. The surface characteristics of three titanium surfaces: smooth (SMO), micro-rough (SLA) and hydrophilic micro-rough (SLActive) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 46 publications
2
30
1
1
Order By: Relevance
“…In this study, early interaction between blood and the 33 implant surface and how this affects the mechanism of osseointegration were investigated. For this, blood 34 coagulation on a micro-roughened hydrophobic titanium (Ti) surface (SLA-H phob ) and on a hydrophilic 35 micro-roughened Ti surface with nanostructures (SLActive-H phil NS), as well as the effects of whole 36 human blood pre-incubation of these two surfaces on the differentiation potential of primary human 37 bone cells (HBC) was assessed. Interestingly, pre-incubation with blood resulted in a dense fibrin network 38 over the entire surface on SLActive-H phil NS but only in single patches of fibrin and small isolated fibre 39 complexes on SLA-H phob .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, early interaction between blood and the 33 implant surface and how this affects the mechanism of osseointegration were investigated. For this, blood 34 coagulation on a micro-roughened hydrophobic titanium (Ti) surface (SLA-H phob ) and on a hydrophilic 35 micro-roughened Ti surface with nanostructures (SLActive-H phil NS), as well as the effects of whole 36 human blood pre-incubation of these two surfaces on the differentiation potential of primary human 37 bone cells (HBC) was assessed. Interestingly, pre-incubation with blood resulted in a dense fibrin network 38 over the entire surface on SLActive-H phil NS but only in single patches of fibrin and small isolated fibre 39 complexes on SLA-H phob .…”
mentioning
confidence: 99%
“…This is of crucial impor-94 tance, since migration of osteoblastic cells occurs through the pro-95 visional fibrin scaffold to reach the protein layer on the implant 96 [31]. 97 Several studies investigated the influence of topographical 98 [32][33][34][35] and physiochemical [36][37][38] Ti surface properties on the 99 adsorption of plasma proteins, the induction of the blood coagula-100 tion cascade and blood-cell adhesion. In particular it was shown 101 that blood clot formation was enhanced on super-hydrophilic Ti 102 surfaces, leading to a dense fibrin network, whereas on hydropho-103 bic Ti surfaces only a thin, non-structured network was observed 104 [37,[39][40][41].…”
mentioning
confidence: 99%
“…29,30 As mentioned above, excellent osseointegration was determined not only by the implant material but also by the surface topography and chemical composition of the implant. 37 From Table 1, the mean surface roughness values were greater on SLActive substrates (around 2 μm) compared with SLA substrates (around 1 μm). 31 Following processing, blood containing a high amount of organic components can adhere more rapidly to the hydrophilic surfaces.…”
Section: Discussionmentioning
confidence: 93%
“…From Table 2 and the AFM 3D images, all surfaces were irregular and rough with uneven peak-to-valley structures, and roughness values of all surfaces were close to 1 μm. 13,14,[37][38][39] Hydroxylation/hydration increases the surface energy/wettability of the implant surface. 43 A moderate surface roughness can promote cell adhesion, differentiation, and the formation of cell matrices.…”
Section: Discussionmentioning
confidence: 99%
“…[101112] Current studies in human bone marrow-derived mesenchymal cells have demonstrated an increase in the gene expression levels of the markers and transcription runt-related factor 2, with bone sialoprotein also observed. [11] In vitro tests show higher cell adhesion on hydrophilic surfaces such as photocatalysis[513] compared to anodized coating with calcium phosphate on hydrophobic surfaces.…”
Section: Introductionmentioning
confidence: 99%